Global New Turkish Lira Bond Issuances - Yuksel Gormez; Gokhan Yilmaz (Turkish Economic Association, 2007)
The objective of this study is to analyze current and likely future impacts of the issuance of New Turkish lira (YTL) denominated borrowing instruments by many global financial institutions around the major financial centres. These bonds are strong source of evidence for international confidence on stabilization efforts in Turkey and they are an indicator of bilateral acceptance of the de facto convertibility of YTL. They may also create an opportunity for the Turkish economy to mitigate negative effects of the original sin
Keywords: E4; E5; E6; G1; 330; Original sin; De facto convertibility; De jure convertibility; New Turkish lira borrowing instruments; Global New Turkish lira issuances; Internationale Anleihe; Währung; Konvertibilität; Türkei